2021
DOI: 10.3390/ijms222112038
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Mutant Preproinsulins Induced Unfolded Protein Response, Gadd45 Expression, JAK-STAT Activation, and Growth Inhibition in Drosophila

Abstract: Mutations in the insulin gene (INS) are frequently associated with human permanent neonatal diabetes mellitus. However, the mechanisms underlying the onset of this genetic disease is not sufficiently decoded. We induced expression of two types of human mutant INSs in Drosophila using its ectopic expression system and investigated the resultant responses in development. Expression of the wild-type preproinsulin in the insulin-producing cells (IPCs) throughout the larval stage led to a stimulation of the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…To examine which one of the two kinases mediates the effects of Paip1 depletion on the ISR, we knocked down individually PERK and GCN2 in a Paip1 depletion background using hh-Gal4 . Previous reported RNAi lines for PERK and GCN2 were used for this analysis [ 37 39 ]. We found that heightened eIF2α phosphorylation in Paip1 -deficient cells was brought to normal levels by PERK knockdown (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine which one of the two kinases mediates the effects of Paip1 depletion on the ISR, we knocked down individually PERK and GCN2 in a Paip1 depletion background using hh-Gal4 . Previous reported RNAi lines for PERK and GCN2 were used for this analysis [ 37 39 ]. We found that heightened eIF2α phosphorylation in Paip1 -deficient cells was brought to normal levels by PERK knockdown (Fig.…”
Section: Resultsmentioning
confidence: 99%